2011
DOI: 10.1055/s-0031-1273394
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E: An Emerging Infectious Disease in Germany?

Abstract: Increased frequencies of HEV infections have been reported in several industrialized countries. We suggest that this finding might be explained by a better awareness of the disease and not by an increased incidence. Although reported HEV infections increased more than 6-fold in Germany in recent years, the seroprevalence remained unchanged (2 %).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…It appears that, at least in the UK, Denmark, and Germany, seroprevalence rates have fallen compared to 20 years ago [26,49,50,51]. There appears to be a cohort effect, related to date of birth, suggesting that high seroprevalence rates seen in the elderly are due to a surge of infection in the 1950s and 1960s.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that, at least in the UK, Denmark, and Germany, seroprevalence rates have fallen compared to 20 years ago [26,49,50,51]. There appears to be a cohort effect, related to date of birth, suggesting that high seroprevalence rates seen in the elderly are due to a surge of infection in the 1950s and 1960s.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, anti-HEV IgG seroprevalence studies from France and the Netherlands found seroprevalence rates of more than 30% [8]. Nevertheless, anti-HEV-IgG seroprevalence has declined in various studies from different industrialized nations over the last 20 years [46,47,48,49]. This contrasts with the rapidly increasing number of reported HEV infections in several industrialized countries over the last decade.…”
Section: Acute Hepatitis E: An Emerging Disease In Western Countries?mentioning
confidence: 99%
“…The discrepancy between decreasing seroprevalence rates and increasing numbers of reported cases indicate that this phenomenon is based on an increased awareness for HEV infections [50]. Based on this assumption, the number of scientific articles on HEV infections has strongly increased since 2006, while i.e., the number of publications on hepatitis A has remained stable [4,47]. Hence, it seems that zoonotic HEV infection in industrialized countries is not emerging but until recently has been an underestimated disease that has, in fact, always been with us.…”
Section: Acute Hepatitis E: An Emerging Disease In Western Countries?mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years from industrialized countries an increased number of autochthonous cases of hepatitis E has been reported. 1 Of note, hepatitis E may take a severe, chronic course in immunosuppressed individuals, as solid organ transplant recipients as well as in HIV-positive individuals. 2–4 Chronic hepatitis E has also been reported in a patient with idiopathic CD4 lymphocytopenia.…”
Section: Introductionmentioning
confidence: 99%